Sommersår hos atlantisk laks (Salmo salar) - Furnesvik, Lisa; Erkinharju, Toni; Larsen, Siw Alvhild; Sæther, Per Anton (Den norske veterinærforening / Norwegian Veterinary Association, 2018)
Journal home page at https://nvt.vetnett.no/ .